HIV infection among children in Malanje province, Angola: a twelve-year follow-up study - Sito, Joaquim; Nunes, Manuel L; Fonseca, Ana Mafalda L (The Journal of Infection in Developing Countries, 2024)
Introduction: Human immunodeficiency virus (HIV) / acquired immunodeficiency syndrome (AIDS) infection has been a serious health problem in pediatric age groups globally, and especially in African countries such as Angola. Our aim was to determine the prevalence rate, accumulate incidence rate, and mortality rate of HIV/AIDS infection in children under 14 years of age residing in four municipalities of Malanje (Malanje, Cacuso, Calandula, and Caculama), from 2010 to 2021. Methodology: This was a documentary research study, with data from 2010 to 2021, developed from a sample size of 10,984 children. Results: The prevalence rate data showed a certain level of dispersion, and no relationship was identified in its behavior over the years (R2 = 0.0036). On the other hand, the accumulate incidence rate presented a tendency to decrease, indicating a moderate level of correlation in its behavior over the years (R2 = 0.4278). Finally, the mortality rate has been decreasing and presented a high correlation in its association with the years under analysis (R2 = 0.8142). Primary schooling and low purchasing power were frequent (60% and 82%, respectively) among the families of HIV-infected children under study. Conclusions: Despite the temporal variation of HIV in children under 14 years of age living in the different municipalities, there was a tendency of its diminishing in the later part of the period, from 2010 to 2021. Nevertheless, the key players should focus on strengthening community strategies for prevention, investigation, and diagnosis of HIV infections in this population.